A Third Order Method for Solving Nonlinear Equations - Foroud Parvaneh (Science Faculty of Chiang Mai University, 2019)
This paper present a third-order family of methods for finding multiple roots of nonlinear. The family requires one-functionand two-derivative evaluation per iteration. These families contain several known third-order methods as special cases. Several numerical examples confirm that the presented methods can be cempetitive to other known methods.